Family Experience Dealing with Relapse in People with Mental Disorders - Ni Made Sri Muryani; I Gede Yudiana Putra; I Kadek Artawan (Babali Nursing Research, 2022)
Introduction: Recurrence is a problem that often occurs in patients with mental disorders. Families who have family members with mental disorders, said that relapse can be caused by not taking medication regularly and when they relapse the family is afraid to face the patient, because the patient is angry and throw things. This study aims to explore in depth the meaning of family experience dealing with relapse in people with mental disorders. Methods: This study uses a qualitative research design with an interpretative phenomenological approach. This study used purposive sampling, with total 15 participants with inclusion criteria: families who have family members with mental disorders who have experienced a relapse in the last six months and are willing to become participants by signing the participant's informed consent form. Exclusion criteria were families with family members with mental disorders who also had other illnesses. The data collection strategy used in-depth interview techniques with semi-structured interview guidelines. Researchers conducted data analysis using Interpretative Phenomenological Analysis (IPA). Results: There are four themes in this study, namely (1) Always pay attention to prevent recurrence, (2) Families are able to recognize signs of relapse in family members with mental disorders, (3) Families use medical health services when a relapse occurs, (4) Feel emotional and fearful when the patient relapses. Conclusion: The results of this study indicate that families feel emotional and fear when the patient experiences a relapse, and the family also knows about the signs of relapse in patients with mental disorders.